Liberia : The World Bank Group Country Opinion Survey FY 2014 - World Bank Group (World Bank, Washington, DC, 2015)
The Country Opinion Survey in Liberia assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Liberia perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral and bilateral agencies, media, academia, the private sector, and civil society in Liberia on: 1) their views regarding the general environment in Liberia; 2) their overall attitudes toward the WBG in Liberia; 3) overall impressions of the WBGs effectiveness and results, knowledge work and activities, and communication and information sharing in Liberia; and 4) their perceptions of the WBGs future role in Liberia.